2017
DOI: 10.5812/semj.13093
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Zinc and Cognitive Impairment in Elderly People of Iran

Abstract: Background: The association between serum zinc levels and cognitive impairment is a controversial issue. Objectives: The association between serum zinc levels and cognitive impairment was investigated in the elderly population of Amirkola city, northern Iran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
2
8
1
Order By: Relevance
“…Our study noted a positive correlation between plasma zinc concentration and AMTS 8 with respect to overall participants and both men and women (r ¼ 0.31, p < 0.001) (r ¼ 0.35, p < 0.001), and (r ¼ 0.29, p < 0.001) respectively, these observations are in line with Markiewicz et al [27], but is in contrast to the study by Kheirkhah et al [36]. Likewise, a recent study that reported that no association was found between zinc concentration in plasma and global cognitive function [29].…”
Section: Discussionsupporting
confidence: 89%
“…Our study noted a positive correlation between plasma zinc concentration and AMTS 8 with respect to overall participants and both men and women (r ¼ 0.31, p < 0.001) (r ¼ 0.35, p < 0.001), and (r ¼ 0.29, p < 0.001) respectively, these observations are in line with Markiewicz et al [27], but is in contrast to the study by Kheirkhah et al [36]. Likewise, a recent study that reported that no association was found between zinc concentration in plasma and global cognitive function [29].…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, a study revealed that advanced PD stage was a risk factor for depressive symptoms in PD patients. 27 Although mental disorders often occur in the elderly with other illnesses, 28 , 29 psychiatric disorders are more frequent in PD patients, especially as the disease progresses. 30…”
Section: Discussionmentioning
confidence: 99%
“…13 In this regard, the results of a study in Iran showed serum zinc level was lower than the normal range at 40.8% of the elderly subjects. 14 With aging populations, age-related health problems will prevail in societies in the near future. Nutritional interventions and effective drug supplements that are used to reduce fatigue in patients and groups are listed as Creatine electrolyte, vitamin B, and a combination of arginine, valine, and serine.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that about 35% to 45% of the elderly over 60 have zinc levels below the normal range 13 . In this regard, the results of a study in Iran showed serum zinc level was lower than the normal range at 40.8% of the elderly subjects 14 . With aging populations, age‐related health problems will prevail in societies in the near future.…”
Section: Introductionmentioning
confidence: 99%